Calliergonella (Bryopsida) in the Iberian Peninsula - Acón, Margarita; Oliván, Gisela; Fuertes, Esther (Botanica Complutensis, 2006)
The genus Calliergonella Loeske is revised for the Iberian Peninsula, based mainly on specimens kept in PC and the main Iberian herbaria. The occurrence of C. cuspidata (Hedw.) Loeske and C. lindbergii (Mitt.) Hedenäs in the studied area is confirmed. C. cuspidata is widely distributed in all kind of wet habitats in the Iberian Peninsula, especially in the mountainous areas of the northern half (30-2000 m a.s.l.). C. lindbergii is restricted to moist ant wet habitats in the Eurosiberian Region, growing from 1200 to 2200 m a.s.l. in the Pyrenees and at lower altitudes (50-100 m a.s.l.) in the Cantabrian Range. A key, descriptions, illustrations and distribution maps of the species of Calliergonella in the Iberian Peninsula are provided.